2016
DOI: 10.1007/s10815-016-0647-y
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcome is optimized by genomic embryo screening, vitrification, and subsequent transfer into a prepared synchronous endometrium

Abstract: Purpose The aim of this study is to compare implantation and live birth rates (LBR) between fresh euploid embryo transfers versus cryo-all cycles with a subsequent embryo transfer into a prepared endometrium. Material and Methods This is a retrospective cohort study. Patients who underwent an IVF cycle with PGS with trophectoderm biopsy from January 2011 to July 2015 were included. Patients were divided into three groups: "Fresh Only," "Frozen Embryo Transfer ('FET) Only," and "Fresh ET then FET." For "Fresh O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 50 publications
(54 reference statements)
1
30
0
3
Order By: Relevance
“…All published studies on the freeze-all policy showed that although this strategy would lead to improvements in IVF outcomes of at least 30% in CPR and OPR when compared to fresh embryo transfers [13,[18][19][20][21][22], there is also a large number of patients that become pregnant even after fresh embryo transfer. To date, there is no effective non-invasive clinical tool that can be used to evaluate endometrial receptivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All published studies on the freeze-all policy showed that although this strategy would lead to improvements in IVF outcomes of at least 30% in CPR and OPR when compared to fresh embryo transfers [13,[18][19][20][21][22], there is also a large number of patients that become pregnant even after fresh embryo transfer. To date, there is no effective non-invasive clinical tool that can be used to evaluate endometrial receptivity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one of the included studies [17] was retracted due to methodological flaws. A recent published study evaluated the freeze-all policy in IVF cycles with preimplantation screening (PGS) and also demonstrated benefit in performing elective cryopreservation of all embryos [19]. A recently published randomized clinical trial (RCT) [20] evaluated 1508 infertile women with the polycystic ovary syndrome who were submitted to a first IVF cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have specifically considered the risk of pregnancy loss following transfer of a mosaic embryo and reported that miscarriage rates are higher than for embryos with a euploid biopsy specimen. The miscarriage rate after transfer of euploid embryos, as classified with the use of NGS, was 6% compared with 13% when aCGH was used (Nisson et al, unpublished data) and 20% with the use of qPCR (31), potentially explained by the inferior ability of aCGH and qPCR to detect mosaicism, resulting in a higher likelihood that affected embryos were transferred. Perhaps more definitively, the study by Fragouli et al (18) showed a miscarriage rate of 55.6% for blastocysts classified as mosaic, versus 17.2% for euploid control samples.…”
Section: Clinical Implications Of Chromosomal Mosaicismmentioning
confidence: 99%
“…Patients who were undertaken two Day 2 or Day 3 cleavage-staged embryos transferred started the progesterone 2 or 3 days before FET, respectively. The vitri cation and thawing procedures were previously described [19]. Embryo transfer was performed via the same exible catheter (20G)and transabdominal ultrasonography guidance.…”
Section: Frozen Embryo Transfer Protocolsmentioning
confidence: 99%